2015
DOI: 10.1186/s13014-015-0363-2
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of anesthesia/sedation in children receiving radiotherapy

Abstract: BackgroundPrevious reports establish low risk of complications in pediatric treatments under anesthesia/sedation (A/S) in the outpatient setting. Here, we present our institutional experience with A/S by age and gender in children receiving daily proton RT.MethodsAfter Institutional Review Board approval, we reviewed our center’s records between 9/9/2004 and 6/30/2013 with respect to age and gender of A/S requirement in our pediatric patients (defined as patients ≤18 years of age).ResultsOf 390 patients treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 15 publications
(15 reference statements)
1
20
0
5
Order By: Relevance
“…A recent study showed that all patients 3 yr and around half those aged 7e8 yr were either sedated or under general anaesthesia during radiotherapy. 4 Ketamine is commonly used for anaesthesia during paediatric neurosurgery 5 and is also used as an effective analgesic or sedative agent. 5e7 There is a specifically vulnerable period during the foetal/ new-born brain development, characterized by synaptogenesis, dendritic arborization, extensive myelinization and biochemical changes, called the 'brain growth spurt' (BGS).…”
mentioning
confidence: 99%
“…A recent study showed that all patients 3 yr and around half those aged 7e8 yr were either sedated or under general anaesthesia during radiotherapy. 4 Ketamine is commonly used for anaesthesia during paediatric neurosurgery 5 and is also used as an effective analgesic or sedative agent. 5e7 There is a specifically vulnerable period during the foetal/ new-born brain development, characterized by synaptogenesis, dendritic arborization, extensive myelinization and biochemical changes, called the 'brain growth spurt' (BGS).…”
mentioning
confidence: 99%
“…Although every measure is taken to eliminate the use of daily anaesthesia, at times it is required. From the literature, GA is advised for patients less than three years of age …”
Section: Methodsmentioning
confidence: 99%
“…However, since it is necessary to perform this procedure several times every day, it is important to properly select subjects considering the risks. On the other hand, while several researchers have reported on the safety and efficacy of general anesthesia during PBT, there is a lack of evidence on the safety of repeated anesthesia and sedation during PBT in children (9)(10)(11). The reports lack information on the equipment standards used for safe general anesthesia management, and there was not enough information on how treatment choices were made at each facility.…”
Section: Treatments Requiring General Anesthesia Besides Surgical Opementioning
confidence: 99%